1995
DOI: 10.1192/bjp.167.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow in Obsessive-Compulsive Disordered Patients at Rest

Abstract: rCBF differs significantly between resting OCD patients and healthy controls, and separate clinical dimensions are associated with functionally distinct rCBF patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Several previous functional imaging studies of OCD have either not assessed the cerebellum , or used the activity in this region as reference for normalizing the radioactive uptake in other brain areas (Lucey et al, 1995;Rubin et al, 1992). However, a PET study of resting glucose metabolism by Swedo et al (1989) reported increases in right cerebellar activity in a sample of early-onset OCD subjects compared with healthy controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several previous functional imaging studies of OCD have either not assessed the cerebellum , or used the activity in this region as reference for normalizing the radioactive uptake in other brain areas (Lucey et al, 1995;Rubin et al, 1992). However, a PET study of resting glucose metabolism by Swedo et al (1989) reported increases in right cerebellar activity in a sample of early-onset OCD subjects compared with healthy controls.…”
Section: Discussionmentioning
confidence: 97%
“…Positron emission tomography (PET) studies measuring resting glucose metabolism have reported hyperactivity in the inferior frontal and anterior cingulate cortices, striatum, and thalamus in patients with OCD (Saxena et al, 1998). There are also single photon emission computed tomography (SPECT) reports of increased (Rubin et al, 1992) or reduced (Lucey et al, 1995) resting regional cerebral blood flow (rCBF) involving frontal-striatal-thalamic circuits in OCD. Finally, there are findings of increased rCBF in inferior frontal, anterior cingulate, striatal, and thalamic areas in PET and functional magnetic resonance imaging (MRI) studies performed during the acute provocation of OCS Rauch et al, 1994).…”
Section: Functional Brain Imaging Studies In Adult Ocd Subjectsmentioning
confidence: 97%
“…Fewer consistent changes were found in basal ganglia: after normalization of data, only three studies found differences in basal ganglia in patients and healthy individuals in the resting state. Increased glucose m etabolism was found by Benkelfat et al (1990) in the left basal ganglia, using PET and bilaterally decreased rCBF by Rubin et al (1992) and Lucey et al (1995) using SPECT.…”
Section: Functional Im Agingmentioning
confidence: 84%
“…In eight of them (Baxter et al, 1987(Baxter et al, , 1988Benekelfat et al, 1990;Machlin et al, 1991;Nordahl et al, 1989;Rubin et al, 1992;Sawle et al, 1991;Swedo et al, 1989b), metabolism or perfusion was reported to be increased in OCD, while it was decreased in the remaining three (Lucey et al, 1995;M artinot, 1990;Mindus et al, 1986). Fewer consistent changes were found in basal ganglia: after normalization of data, only three studies found differences in basal ganglia in patients and healthy individuals in the resting state.…”
Section: Functional Im Agingmentioning
confidence: 93%
“…Finally, Lucey et al (1995), using SPECT, compared 30 OCD patients with 30 healthy control subjects and found decreased metabolic activity in the right caudate nucleus and the right thalamus, as well as in several cortical areas, including the right inferior frontal cortex.…”
Section: Functional Brain Imagingmentioning
confidence: 99%